Wearable monitors for patients following discharge from an intensive care unit: practical lessons learnt from an observational study. (18th March 2016) - Jeffs, Emma; Vollam, Sarah; Young, J. Duncan; Horsington, Lois; Lynch, Breda; Watkinson, Peter J.
Abstract: Aims: To identify the practical challenges encountered when using wearable monitors for patients discharged from the intensive care unit. Background: Patients discharged from intensive care units are a high‐risk group that might benefit from continuing observation using 'wearable' monitors to enable faster identification of physiological deterioration and facilitate timely clinical action. This area of technological innovation is of key interest to nurses who manage this group of patients. Design: A prospective observational study. Methods: An observational study conducted in 2013–2014 used wearable monitors to record continuous observations for patients discharged from an intensive care unit to develop a predictive model of patients likely to deteriorate. Screening data for study eligibility and case report form data to assess monitor tolerance and comfort were collected daily and analysed using Microsoft Access. Results/findings: Patients ( n =  2704) were discharged from an intensive care unit during the study, 208 consented to wearing the monitor. Of the 192 included in analysis, 130 (67·7%) removed the monitor before the trial finished. Reasons cited for removal included 'discomfort and irritation' 61 (31·8%) and 'feeling too unwell' 8 (4·2%). Five hundred seventeen patients were screened following adaption of the wearable monitor. Despite design changes, 56 (10·8%) patients were unable to wear monitors for reasons related to their anatomy or condition. Of 124 patients, 65 patients (52·4%) who were approached refused participation. Conclusion: Work is needed to understand wireless monitor comfort and design for acutely unwell patients. Product design needs to develop further, so patients are catered for in flexibility of monitor placement and improved comfort for long‐term wear.